Effect of Cooling Water Fraction Of Salt in Low Carbon Steel Properties - Ahmadin Ahmadin; Diah kusuma pratiwi (Universitas Sriwijaya, 2015)
Low carbon steel plate is widely used in the field of construction that require high hardness and ductility . One method used to increase the hardness of the low carbon steel plate that is by quenching water plus salt . The results showed that the quenching is based on a study of 10% salt water has a hardness of 168 VHN with Ïƒu = 33.62 , Îµ = 12 % and the lowest is 15 % salt water quenching VHN 101 Ïƒu = 30.30 and Îµ = 7.30% composition of the study above was 10 % salt solution in the cooling water will cause a decrease in mechanical properties .